360-Degree Evaluation of a Primary Healthcare Centre Village Stay Programme for Medical Undergraduates - Dinesh Kumar; Uday S Singh; Tushar Patel; Manisha Gohel (Medsci Publications, 2018)
Background: Indian Medical Graduates are expected to work as Medical officersat Primary Health Centres (PHC). However, their current training provides inadequate opportunity for practical un- derstanding of PHC, especially the administrative aspects. Methods: Medical Undergraduates (3rd MBBS, part 1) were posted at four PHCsfor four days. Orientation sessions and post visit presentation were carried out one day before and after the residen- tial posting. Teaching was by group discussions, informal interac- tions with the local communities, interview of the PHC staff, ob- servation of the activities, analysis of various PHC records and re- ports, mainly as self-directed activities. Pre and post-test were conducted to assess the gain in knowledge. Results: Mean pre-test score was 6.50 (SD=1.93) and post test score was 11.7 (SD=1.41). There was significant improvement in scores [5.20 (SD=2.25), p<0.001, Wilcoxon sign rank test). Programme was appreciated by students, villagers, PHC medical officers and the facilitators. Main problems identified were logistic issues, hectic schedule and expectations from the villagers. Conclusions: The PHC village stay is an effective and acceptable teaching strategy for better understanding of rural health issues. The local community, PHC staff and Facilitators appreciated the programme.